ANALISIS PERANAN PAJAK PARKIR DALAM UPAYA MENINGKATKAN PENDAPATAN ASLI DAERAH KOTA MEDAN - Fahani, Tania Azura; Rahmani, Nur Ahmadi Bi (Cattleya Darmaya Fortuna, 2025)
One type of local tax is parking tax, which is intended to support effective parking management and increase local revenue. Local revenues, taxes, proceeds from the management of special property, and other legal revenues are part of local revenue. To support regional autonomy, governments pay local taxes.A descriptive qualitative methodology was employed in this investigation. Interviews and documentation were used to gather data. To conduct this analysis, previous reviews were considered. The results showed that although parking tax increased Medan city's revenue, it had no impact on local own-source revenue.